Issues in equivalence: Information literacy and the distance student - Lamond, Heather; White, Bruce (Distance Education Association of New Zealand, 2008)
Information Literacy is a recognised lifelong learning skill, and an expected graduate attribute. With the growth in distance provision of tertiary education it is important to acknowledge the barriers faced by distance students and the difficulties libraries face in delivering equivalent learning opportunities to students who are physically isolated from their institution. This paper outlines the importance of information literacy, the major barriers faced by distance students and makes suggestions as to how institutions and their libraries can better meet their learning needs.
Keywords: Distance education; Information literacy; Fields of Research::330000 Education